Gall bladder Ascariasis: A rare entity - S. Gyawali (Elsevier, 2021)
Gall bladder ascariasis is a rare entity. The causative organism for gall bladder ascariasis is Ascaris lumbricoides It usually presents as acute acalculous cholecystitis. Conservative management with anti-helminthic drugs is preferred while sometimes the patient may need surgical intervention.